Foreign Exchange Trading Menurut Dewan Syariah Nasional Nomor 28/DSN-MUI/III/2002 Tentang Jual Beli Mata Uang (al-Sharf) (Studi Kasus PT Valbury Asia Future) - Moh. Toha Munir; Misno (Institut Agama Islam Sahid Bogor, 2022)
In the era of the industrial revolution 4.0, all information and technology can be accessed online quickly. And it is undeniable that slowly everything has shifted towards digital, so that human and technology interactions cannot be avoided anymore. All fulfillment needs are now available digitally, such as buying and selling, services to payment transactions, even buying and selling currencies (al-Sharf) can be done online. This is what led the author to analyze the foreign exchange trading (al-Sharf) carried out at PT Valbury Asia Future. Has PT Valbury implemented the MUI DSN fatwa in carrying out the transaction? Therefore, the author tries to raise the title in his research, namely Foreign Exchange Trading According to the National Sharia Board Number 28 / DSN-MUI / III / 2002 concerning Currency Trading (al-Sharf) (Case Study of PT Valbury Asia Future). In this thesis the writer uses the Normative Legal Studies approach. What is meant by Normative Legal Studies research is a research method used to examine the object of research based on legal norms. The method used in data collection in this study is the book survey method / library research (library research). This study aims to systematically describe the forms of transactions carried out by PT Valbury Asia Future and the law of foreign exchange trading transactions according to the DSN MUI fatwa Number 28 / DSN-MUI / III / 2002 concerning currency trading (al-Sharf). Then it was concluded that the types of transactions allowed in foreign exchange trading according to the DSN MUI fatwa Number 28 / DSN-MUI / III / 2002 are spot transactions, while forward, swap and option transactions are haram.